Integrating Mobile Learning and BOM ATOM Model in Teaching Observational Report Texts at Vocational High Schools - Erika Kurniawati; Syamsul Sodiq; Titik Indarti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the application of mobile learning Tangkas Berobservasi model BOM ATOM in learning to write observation report text in class X SMK. The rapid advances of technology in the learning process require students to have digital literacy which is not only the ability to operate devices, but also the skills in understanding, using, and critically interacting with information and communication technology. In the context of learning, mobile learning is one of the innovative solutions that allows flexible access to materials anytime and anywhere. The implementation of Mobile learning Tangkas Berobservasi based on the BOM ATOM model in learning observation report text in vocational is one of the learning solutions with technology integration. This media is designed to develop students' critical, analytical, and collaborative thinking skills through the use of digital technology. This research uses a qualitative approach with interview and observation methods as data sources. The results showed that the use of Android-based Tangkas Berobservasi mobile learning is suitable for students' needs and able to improve digital literacy. In addition, this technology-based learning provides convenience in accessing materials, improving concept understanding, and supporting digital interaction and collaboration in the learning process. The implementation of BOM ATOM model in mobile learning also helps students in organizing information, developing reflective skills, and increasing active participation in learning.